2013
DOI: 10.3390/md11030870
|View full text |Cite
|
Sign up to set email alerts
|

The Protection of Polysaccharide from the Brown Seaweed Sargassum graminifolium against Ethylene Glycol-Induced Mitochondrial Damage

Abstract: The aim of the present study is to evaluate the protective effect of polysaccharide from the Brown Seaweed Sargassum graminifolium (SGP) on ethylene glycol-induced kidney damage and the mechanism of SGP-mediated protection. Mitochondrial lipid peroxidation, mitochondrial swelling, the activity of succinate dehydrogenase (SDH), ATPases and mitochondrial antioxidant enzymes was observed in hyperoxaluric rats. Administration of SGP (25, 100 and 400 mg·kg−1, intragastrically) increased the activities of antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…A symbolic event in early apoptosis is the decrease in mitochondrial membrane potential (Δ Ψ m). JC-1 differentially labels mitochondria with high and low Δ Ψ m by forming J-aggregates or monomers that emit orange-red or green light, respectively [ 37 ]. The Δ Ψ m and concentration of J-aggregates were high in the mitochondria of living cells.…”
Section: Resultsmentioning
confidence: 99%
“…A symbolic event in early apoptosis is the decrease in mitochondrial membrane potential (Δ Ψ m). JC-1 differentially labels mitochondria with high and low Δ Ψ m by forming J-aggregates or monomers that emit orange-red or green light, respectively [ 37 ]. The Δ Ψ m and concentration of J-aggregates were high in the mitochondria of living cells.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that accumulation of ROS in vivo can attack cells and cause protein oxidation, lipid peroxidation, and nucleic acid fracture, which can affect normal cell functions and result in the occurrence of chronic diseases [46, 47, 76]. As antioxidants, polysaccharides can scavenge radicals, reduce oxidative damage of cells, and exhibit protective effects on cells [77]. For instance, Lycium barbarum polysaccharides can protect tissue cells from DNA damage induced by oxidative stress [78].…”
Section: Discussionmentioning
confidence: 99%
“…bisacetylenic alcohol ( 191 ) [184]; conicasterol E ( 192 ) [185]; 6”-debromohamacanthin A ( 193 ) [186]; dieckol ( 194 ) [187]; fructigenine A ( 195 ) [188]; geoditin A ( 196 ) [189]; gorgosterol ( 197 ) [190]; gracilioether B ( 198 ) [191]; gracilioether K ( 199 ) [192]; herdmanine K ( 200 ) [193]; hyrtioreticulin A ( 201 ) [194]; new Kunitz-type protease inhibitor InHVJ ( 202 ) [195]; jaspamide ( 203 ) [196]; latonduine A ( 204 ) [197]; leucettine L41 ( 205 ) [169]; manzamine A ( 206 ) [198]; nahuoic acid A ( 207 ) [199]; namalide ( 208 ) [200]; ningalins C and D ( 209 , 210 ) [201]; octaphlorethol A ( 114 ) [120]; petrosaspongiolide M ( 211 ) [202]; petrosiol A ( 212 ) [203]; phidianidine A ( 213 ) [204]; Poly-APS ( 214 ) [205]; Pseudoceratina sp. dibromotyrosine ( 215 ) [206]; pseudopterosin A ( 216 ) [207]; sargachromanol G ( 217 ) [208]; S. graminifolium polysaccharide ( 218 ) [209]; S. patens phloroglucinol ( 219 ) [210]; S. xiamenensis benzopyran ( 220 ) [211]; theonellasterol ( 221 ) [212]; toluquinol ( 222 ) [213]; and U. lactuca fatty acid ( 223 ) [214]. …”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%